Foreign investment in Vietnam : Juridical bases - Present state - Opportunities - Prospects - Nguyen Anh Tuan; Phan Huu Thang; Hoang Van Huan (H. The gioi, 1994)
Content: Juridical aspect of foreign investment activities in Vietnam; Foreign in vestment activities in Vietnam in the years 1988-1993; Export production zones in Vietnam; Prospects of foreign investmenr in Vietnam until 2000
Keywords: Luật học